A Novel Technique for Constructing Difference Schemes for Systems of Singularly Perturbed Equations. (17th May 2016) - Hsieh, Po-Wen; Shih, Yin-Tzer; Yang, Suh-Yuh; You, Cheng-Shu
Abstract: In this paper, we propose a novel and simple technique to construct effective difference schemes for solving systems of singularly perturbed convection-diffusion-reaction equations, whose solutions may display boundary or interior layers. We illustrate the technique by taking the Il'in-Allen-Southwell scheme for 1-D scalar equations as a basis to derive a formally second-order scheme for 1-D coupled systems and then extend the scheme to 2-D case by employing an alternating direction approach. Numerical examples are given to demonstrate the high performance of the obtained scheme on uniform meshes as well as piecewise-uniform Shishkin meshes.